Mary Frances Crowley: Vision, Values and Principles still alive and fl ourishing? - Carney M; Clune Mulvaney C; Kearns T (Archives of Nursing Practice and Care - Peertechz Publications, 2017)
Summary: Mary Frances Crowley nurse, midwife and nurse and midwifery tutor was founder member and first Dean of the Faculty of Nursing and Midwifery in the Royal College of Surgeons in Ireland. She started the Medical Missionaries Midwifery Training School at the International Hospital, Drogheda in 1942. She was a visionary who was instrumental in the development of education and professional development for nurses and midwives in Ireland. She lived and worked by her values and principles and expected others to do likewise. Background: A Faculty of Nursing of the RCSI was a vision Miss Crowley nurtured for many years until its fruition in 1974. The Faculty was her creation, offering studies at the highest level of professional and academic excellence for nurses, when few colleges had yet to start introducing programmes for nurses. The Faculty is recorded as a milestone in the development of Irish nursing due to her foresight and dedication to early nursing education and in promoting ethical principles. Aim: The Commentary to the Editor seeks to obtain the views of scholars in relation to the content presented here. The commentary provides insights into the life and legacy of Mary Frances Crowley a forward thinking nurse, midwife and inspiring leader whose nursing career was governed by Christian values. Research Methods: This literature review undertaken in 2016, explores the work and writings of Miss Crowley. Searches were undertaken in archives and libraries in the Royal College of Surgeons in Ireland and in hospitals where she worked. Implications for nursing: This study highlights how nurses' of vision, holding ethical values aimed at providing care that enshrines responsibility for professional conduct. Findings will inspire patients